G protein‐coupled receptors can control the Hippo/YAP pathway through Gq signaling. Issue 7 (11th June 2021) - Zindel, Diana; Mensat, Patrick; Vol, Claire; Homayed, Zeinab; Charrier‐Savournin, Fabienne; Trinquet, Eric; Banères, Jean‐Louis; Pin, Jean‐Philippe; Pannequin, Julie; Roux, Thomas; Dupuis, Elodie; Prézeau, Laurent
Abstract: The Hippo pathway is an evolutionarily conserved kinase cascade involved in the control of tissue homeostasis, cellular differentiation, proliferation, and organ size, and is regulated by cell‐cell contact, apical cell polarity, and mechanical signals. Miss‐regulation of this pathway can lead to cancer. The Hippo pathway acts through the inhibition of the transcriptional coactivators YAP and TAZ through phosphorylation. Among the various signaling mechanisms controlling the hippo pathway, activation of G12/13 by G protein‐coupled receptors (GPCR) recently emerged. Here we show that a GPCR, the ghrelin receptor, that activates several types of G proteins, including G12/13, Gi/o, and Gq, can activate YAP through Gq/11 exclusively, independently of G12/13. We revealed that a strong basal YAP activation results from the high constitutive activity of this receptor, which can be further increased upon agonist activation. Thus, acting on ghrelin receptor allowed to modulate up‐and‐down YAP activity, as activating the receptor increased YAP activity and blocking constitutive activity reduced YAP activity. Our results demonstrate that GPCRs can be used as molecular switches to finely up‐ or down‐regulate YAP activity through a pure Gq pathway.